Outcome of Twin Pregnancy in a Periurban Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To determine the socio demographic characteristics, clinical presentation and obstetric outcome at delivery and immediate postpartum period of twin gestation in a periurban hospitalMaterial & Methods: An observational study was conducted between January 2000 to December 2004 at Institute of Child and Mother Health. All twin pregnancy irrespective of gestational age admitted in the in-patient department of Institute of Child and Mother Health for delivery and also those undiagnosed cases found to have twin birth were enrolled in the study consecutively from January 2001 to December 2004. Data on socio-demographic factors, predisposing factors for twin gestation and obstetric characteristics was collected using a structured questionnaire. Hospital records were consulted for recording the investigation reports and management options. The outcome variables were maternal complications during antenatal, intranatal and immediate postnatal period, mode of delivery, birth weight and sex of newborn and fetal outcome. All twin pregnancies from the admitted obstetric patients were enrolled consecutivelyResults: During the study period there were 11,185 deliveries and among them 107 were twin gestation. About 22% were primigravida, 78.5% multigravida, 27.1% were illiterate. Most common age group were 24-29 years (39.4%). Antenatal care was availed by 71% of patients and 27.1% twins were not diagnosed till delivery. Family history of twin on maternal side was present in 58.1% and 31.8% had history of taking oral contraceptive immediately before the pregnancy. Ovulation inducing agents were given to 8.3% of twin. Presentations of fetus were both vertex 54.2%, 1st vertex and second breech 16%, and both breech 5.7%. About 55.1% were admitted with labor pain, 6.5% were undelivered second twin. Preterm birth was 27.2% and low birth weight of 1st baby 79.6% and second baby 80.9% respectively. Mode of delivery was vaginal delivery of both fetus 41.6%, caesarean section of both fetus 62.4%, and caesarean for second twin 3.1%. Same sex of both twins was found in 78% and male-male pair was 50%. There was one stillbirth, one conjoined twin and perinatal death was 11.2% Complications encountered during perinatal period were severe abdominal pain 9.3%, retained placenta in 7.3%; and post partum hemorrhage in 4.6% cases.Conclusion: Twin pregnancy is quite common and warrants specialized care during ante partum, intrapartum and postpartum period.Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 57-62